How can critical consciousness influence community driven development as social innovation? - Docrat, Noor Jehan (Graduate School of Business (GSB), 2026)
This research sought to understand how unsustainable popularised models of development which focuses on funder priorities and current organisational strategy while excluding the community's input in core decision-making regarding funding, development, and resource allocation (Everatt, 2005; Pham, 2018; Wilkinson-Maposa, 2017) can be restructured to include the community. The researcher framed the research under the Community Driven Development (CDD) approach which has emerged as an innovative, inclusive, and sustainable approach to facilitate and drive community development. The approach acknowledges that the community is the heart of the transformative process, favouring decentralisation and leading from the community's perspective (Asmorowati, 2011). In particular, CDD supports the idea that to get to the root cause of problems/oppressive inequalities, the community identifies and formulates critical questions and subsequently derives a unique set of objectives to accomplish the objectives (Torjman et al., 2012). Despite the encouraging goals and motivations behind CDD, critiques of community-led development doubt its efficacy (Pham, 2018). Ironically, CDD evaluation of the impact and success of a project goes against its values of inclusivity and participation. Instead, it is a top- down, pre-determined concept designed by outside stakeholders, with local community members having no say in what or how evaluations are measured (Pham, 2018). In response to the shortcomings of CDD, the researcher included the constructs of critical consciousness (CC) into the research since CC also has emerged as an antidote to social inequalities (Shin et al., 2016). Grounded in the educational pedagogy developed by Brazilian educator Paulo Freire, critical consciousness enables marginalised communities to navigate and resist unequal and oppressive structures and systems by critically reflecting on their perception of reality and taking action to overcome this (Heberle et al., 2020). Community- driven development expands from the CC approach and can be viewed as the action part of CC because of the progressive, inclusive, and integrative principles and practices that shift the power, decision-making, and resources to the hands of the community. Like CC, CDD focuses on the intrinsic elements of self-determination and human rights (Casey, 2018). As CDD and CC follow similar fundamental philosophies, drawing parallelism between both can unlock innovative and sustained processes. However, related literature on critical consciousness advances extensively on critical reflection; but limited research focuses on community action as an essential component of consciousness (Hope & Bañales, 2019; Watts et al., 2011). Broadening on this discussion, the researcher wanted to explore the emergence of innovation characteristics, particularly social innovation, which can reform the developmental landscape. Social innovation can be seen as an effective way of responding to the challenges and inequities marginalised societies face (Avelino et al., 2019) by creating news ways of doing, creating knowledge, and arranging resources to develop creative solutions to social inequities (Nordberg et al., 2020). However, how CC manifests in CDD macro organisations through communities is unclear. Moreover, although there are several intersectionalities between CC and CDD, CDD organisations are still an underexplored field of research. In focusing on Critical consciousness as a tool for social innovation and exploring how it emerges in an organisational and community setting, this research shed light on the mechanisms, processes, and outcomes driving community development change. By focusing my research on CDD, which is driven by community action, it is hoped that my research will gain valuable insights and future pathways in CC and CDD, including barriers and transformative potential for social innovation. The research question is: How can Critical Consciousness Influence Community Driven Development as social innovation? This research fulfilled the conditions of using the case study strategy since the research question is explanatory in asking a “how” question related to a contemporary phenomenon (how can critical consciousness influence community driven development as social innovation?). The research used multiple sources of evidence (semi-structured interviews, observations, and documents) as tools for gathering data. The unit of analysis in this study was the community driven development project undertaken in a specific context. This study is an embedded multiple case study design of three community-driven development projects. The participants include donors or funders, various stakeholders of the organisation facilitating the community-driven development project, and community members and beneficiaries of the CDD project. This research inquiry used the thematic analysis process documented by Braun & Clarke, 2006, which was an iterative, recursive, and reflective process.